(untitled) (Scientific journal of the Fergana State University, 2024)
Art pedagogy with its research and educational methods is currently actively developing at the initial stage and has an excellent place in the system of general and additional education. This article examines the concept of art pedagogy, which entered the field of science as a result of pedagogical technologies in the field of education, as well as its place and role in increasing the creative competence of future teachers.